Negative plate, preparation method thereof and battery
By sequentially coating the first active layer and the second active layer on the current collector of the negative electrode sheet, the combination of single-wall carbon nanotubes and double-bonding agents is used to solve the problem of easy expansion of the silicon-based material, and the high cycle performance and structural safety of the battery are achieved.
Patent Information
- Application Number
- CN202411856960.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-21
AI Technical Summary
The theoretical capacity of existing graphite negative electrode materials is limited, and the silicon-based materials are prone to expand, resulting in reduced battery circulation performance and structural safety threats.
The first active layer and the second active layer structures are sequentially coated on the current collector. The first active layer contains a single-wall carbon nanotube and a double-bonding agent. The second active layer also contains a single-wall carbon nanotube. Through the structure and material combination of these layers, the expansion and delamination of the negative electrode material are suppressed and the circulation performance of the battery is improved.
It effectively suppresses the expansion of the negative electrode sheet, improves the circulation performance and structural safety of the battery, and meets the needs of higher energy density.
Smart Images

Figure CN119673964A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a negative electrode sheet and a preparation method thereof, and a battery. Background Art
[0002] In the research and development of solid-state batteries, the selection and design of negative electrode materials are crucial. Graphite, as the mainstream negative electrode of the battery, is limited by the nature of its material, and its theoretical gram capacity is only 372mAh / g. Moreover, some of the graphite negative electrodes currently developed are close to their limits and cannot meet the current demand for higher energy density. Therefore, people have turned their attention to silicon-based materials (the theoretical gram capacity of pure silicon is 4200mAh / g), but because silicon-based materials are easy to expand, with the increase of silicon content, especially when the silicon content reaches more than 10%, during the cycle, with the increase of the number of charge and discharge cycles, the silicon-based materials inside the battery expand severely, which can easily lead to a sharp increase in the expansion force of the pole piece & battery, deteriorating the pole piece interface and the internal interface of the negative electrode material particles, resulting in a cycle dive; at the same time, the expansion force is too large, which is also a huge challenge to the safety of the battery module / Pack structure. Summary of the invention
[0003] Based on this, the present application provides a negative electrode sheet and a preparation method thereof, and a battery to solve the above technical problems.
[0004] A first aspect of the present application provides a negative electrode sheet, which includes a current collector and a first active layer and a second active layer sequentially arranged on the surface of the current collector;
[0005] The first active layer includes a first active material, a first conductive agent and a first binder, wherein the first binder is a mixture of a binder A and a binder B;
[0006] The second active layer includes a second active material, a second conductive agent and a second binder, and the second conductive agent includes a single-arm carbon nanotube.
[0007] In some embodiments, the first conductive agent includes single-walled carbon nanotubes.
[0008] In some embodiments, binder A and binder B are different binders, and binder A includes at least one of a PAA-based binder or an SBR-based binder;
[0009] The binder B includes at least one of a PAA-based binder and a SBR-based binder.
[0010] In some embodiments, in the first binder, the mass ratio of binder A to binder B is 1:3.
[0011] In some embodiments, the mass ratio of the first conductive agent to the first binder is 1:4; the mass ratio of the second conductive agent to the second binder is 1:3.
[0012] In some embodiments, the first active material includes one or more of pure silicon, silicon alloy, silicon-carbon composite material, silicon-oxygen composite material; the second active material includes one or more of pure silicon, silicon alloy, silicon-carbon composite material, silicon-oxygen composite material.
[0013] In some embodiments, the second conductive agent further includes conductive carbon black SP.
[0014] In some embodiments, the mass percentage of the first active material and the first binder is (93%-97%): (2%-5%).
[0015] In some embodiments, the mass percentage of the second active material and the second conductive agent is (93%-97%): (1%-2%).
[0016] The second aspect of the present application provides a method for preparing a negative electrode sheet as provided in the first aspect, comprising the following steps:
[0017] S1, mixing a first active material, a first binder, and a first conductive agent to form a first slurry;
[0018] S2, mixing a second active material, a second binder, and a second conductive agent to form a second slurry;
[0019] S3, sequentially coating the first slurry and the second slurry on the current collector;
[0020] S4. Drying to obtain the negative electrode sheet.
[0021] The third aspect of the present application provides a battery, comprising a positive electrode sheet, a negative electrode sheet and a solid electrolyte membrane, wherein the negative electrode sheet is the negative electrode sheet provided in the first aspect or the negative electrode sheet prepared according to the preparation method provided in the second aspect. The positive electrode sheet and the negative electrode sheet are stacked crosswise, and the solid electrolyte membrane is arranged between the positive electrode sheet and the negative electrode sheet.
[0022] In this application, single-walled carbon nanotubes are arranged in the second active layer to wrap the second active material particles, thereby inhibiting the expansion of the second active material particles and preventing the second active layer from expanding and deforming. In addition, the second active layer that is not easily deformed is arranged on the side of the first active layer away from the current collector, which can produce a certain restraining effect on the first active layer, inhibit the expansion of the first active layer, and improve the battery cycle performance. In addition, single-walled carbon nanotubes are also added to the first active layer to coat and restrain the active material particles in the first active layer, which can further restrain the expansion of the first active layer and improve the battery cycle performance.
[0023] On the other hand, two additives are added to the first active layer to increase the bonding effect between the first active layer and the second active layer and the current collector, prevent the negative electrode sheet from falling off, and further improve the battery cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a flow chart of a method for preparing a negative electrode sheet in one embodiment of the present application. DETAILED DESCRIPTION
[0025] References to embodiments of the present application will now be provided in detail, one or more embodiments of which are described below. Each embodiment is provided as an explanation rather than a limitation of the present application. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present application without departing from the scope or spirit of the present application. For example, a feature described or described as part of one embodiment may be used in another embodiment to produce a further embodiment.
[0026] Therefore, it is intended that the present application covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present application are disclosed in or are apparent from the following detailed description. It will be appreciated by those of ordinary skill in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the present application.
[0027] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0028] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0029] In this article, when referring to the unit of a data range, if there is a unit only after the right endpoint, it means that the units of the left and right endpoints are the same. For example, 100~150 nm means that the units of the left endpoint "100" and the right endpoint "150" are both nm (nanometers).
[0030] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0031] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0032] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, mentioning that the method may also include step (c) means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0033] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0034] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0035] The first aspect of the present application provides a negative electrode sheet, which includes a current collector and a first active layer and a second active layer sequentially arranged on the surface of the current collector; wherein,
[0036] The first active layer includes a first active material, a first conductive agent and a first binder, wherein the first binder is a mixture of a binder A and a binder B;
[0037] The second active layer includes a second active material, a second conductive agent and a second binder, and the second conductive agent includes single-walled carbon nanotubes.
[0038] The present application provides single-walled carbon nanotubes in the second active layer to wrap the second active material particles, thereby inhibiting the expansion of the second active material particles and preventing the second active layer from expanding and deforming. The second active layer that is not easily deformed is provided on the side of the first active layer away from the current collector, and a binder A and a binder B are provided in the first active layer to enhance the bonding effect between the first active layer and the current collector and the first active layer, so that the second active layer interacts with the current collector to jointly inhibit the expansion of the first active layer and improve the battery cycle performance.
[0039] In some embodiments, the first conductive agent included in the first active layer can make the electrode conductive.
[0040] Specifically, the first conductive agent may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., such as copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof. In some preferred embodiments, the first conductive agent includes single-walled carbon nanotubes. By adding single-walled carbon nanotubes to the first active layer, not only can the conductivity of the first active layer be improved, but the single-walled carbon nanotubes can also wrap and restrain the first active material particles, inhibit the expansion of the first active material particles, and thus prevent the expansion and deformation of the first active layer. At the same time, combined with the constraints of the second active layer and the current collector on the first active layer, the expansion and deformation of the first active layer can be further prevented. And then the expansion force of the negative electrode sheet as a whole can be reduced to ensure the cycle performance of the battery.
[0041] In some embodiments, binder A and binder B are different binders; binder A includes at least one of a PAA-based binder or a SBR-based binder; and binder B includes at least one of a PAA-based binder or a SBR-based binder.
[0042] In some specific implementations, binder A is an SBR binder, and binder B is a PAA binder.
[0043] Among them, the SBR-type binder can interact with the carbon nanotubes on the surface of the second negative electrode active layer, thereby significantly improving the bonding force between the surface of the first active layer and the surface of the second active layer; and, the SBR-type binder can also improve the bonding force between the first active layer and the current collector, so that the first active layer is not easy to fall off from the current collector, which helps to increase the constraint of the current collector and the second active layer on the first active layer. On the other hand, the PAA-type binder plays a thickening role in the first active layer, which can improve the bonding force between the components inside the first active layer, and can prevent the problem of internal cracking caused by expansion of the first active layer, so that the first active layer is not only bound by the current collector and the second active layer, but also by its own binder, further preventing the expansion of the first active layer. In summary, adding SBR-type binders and PAA-type binders in the first active layer helps prevent the expansion of the negative electrode sheet and improve the battery cycle performance. In some embodiments, in the first binder, the mass ratio of binder A to binder B is 1:3.
[0044] When the mass ratio of binder A to binder B exceeds this range, if the amount of SBR binder decreases, it is easy to affect the bonding effect between the first active layer and the current collector and the second active layer, resulting in the first active layer being easily separated from the current collector and / or the second active layer, and the negative electrode sheet being delaminated, affecting the battery cycle performance. In addition, when the mass ratio of binder A to binder B is not within this range, if the amount of PAA binder decreases, it is easy to cause cracking inside the first active layer, which will still cause the negative electrode to be delaminated, affecting the battery cycle performance.
[0045] In some embodiments, the mass percentage of the first binder to the first conductive agent is 1:4, and the mass percentage of the first binder to the first conductive agent is 1:3.
[0046] In some embodiments, the first active material includes at least one of silicon-based negative electrode materials, pure silicon, silicon-oxygen negative electrode materials, silicon-carbon negative electrode materials, and silicon alloy negative electrode materials.
[0047] The first active material also includes at least one of natural graphite, artificial graphite, soft carbon, and hard carbon.
[0048] Considering the large volume change rate of silicon-based materials, the present application also discloses in some embodiments that silicon-based materials are mixed with carbon-based materials to form a composite active material. The composite active material has a smaller volume change rate, is relatively less prone to pulverization, and has better stability. At the same time, compared with pure carbon-based materials, its gram capacity is significantly improved, which is conducive to improving the energy density of the battery. On the other hand, carbon-based materials have good electrical conductivity, which can also improve the conductivity of the negative electrode sheet, helping to improve the energy density of the battery.
[0049] In some preferred embodiments, the first active material includes graphite and silicon, and the mass ratio of graphite to silicon is (70-80): (20-30).
[0050] When the mass ratio is greater than this range, the mass of silicon decreases, and the gram capacity of the electrode decreases; when it is less than this range, the mass of graphite decreases, which will affect the expansion rate of the negative electrode sheet, easily causing the negative electrode to expand, and also affect the conductivity of the battery.
[0051] In some embodiments, the second active material includes at least one of pure silicon, silicon-oxygen negative electrode material, silicon-carbon negative electrode material, and silicon alloy negative electrode material. In the present application, by using silicon-based negative electrode in both the first active layer and the second active layer, the gram capacity of the battery can be guaranteed. And the single-walled carbon nanotubes in the first active layer, the double binder, and the addition of single-walled carbon nanotubes in the second active layer work synergistically to inhibit the expansion of the negative electrode sheet and ensure the cycle performance of the battery.
[0052] The second active material also includes at least one of natural graphite, artificial graphite, soft carbon, and hard carbon.
[0053] Due to the large volume change rate of silicon-based materials, the present application also discloses in some embodiments that silicon-based materials are mixed with carbon-based materials to form a composite active material as the second active material. This composite active material has a smaller volume change rate, is relatively less prone to pulverization, and has better stability. At the same time, compared with pure carbon-based materials, its gram capacity is significantly improved, which is beneficial to improving the energy density of the battery. On the other hand, carbon-based materials have good electrical conductivity, which can also improve the conductivity of the second active layer, helping to improve the energy density of the battery.
[0054] In some preferred embodiments, the second active material includes graphite and silicon, and the mass ratio of graphite to silicon is (70-80):(20-30).
[0055] When the mass ratio is greater than this range, the mass of silicon decreases, and the gram capacity of the electrode decreases; when it is less than this range, the mass of graphite decreases, which will affect the expansion rate of the negative electrode sheet, easily causing the negative electrode to expand, and also affect the conductivity of the battery.
[0056] In some embodiments, the second conductive agent further includes one or more of conductive carbon black SP, acetylene black, conductive graphite, and graphene.
[0057] Preferably, the second conductive agent further comprises conductive carbon black SP. Adding conductive carbon black SP to the second active layer can greatly improve the conductive performance of the second active layer.
[0058] In some embodiments, the second binder included in the second active layer can improve the bonding between the second active material particles and the carbon nanotubes, and the bonding between the negative electrode active material and the first active layer.
[0059] In some embodiments, non-limiting examples of the second binder include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, and the like.
[0060] In some embodiments, the mass percentage of the first active material and the first binder is (93%-97%): (2%-5%).
[0061] In some embodiments, the mass percentage of the second active material and the second conductive agent is (93%-97%): (1%-2%).
[0062] In some embodiments, the negative electrode current collector can be selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.
[0063] In the present application, a first binder including a binder A and a binder B is provided in the first active layer, and a carbon nanotube conductive agent is provided in the second active layer. On the one hand, the carbon nanotube conductive agent is provided in the second active layer, and the carbon nanotubes can wrap the second active material particles, inhibit the expansion of the second active material particles, and then reduce the expansion force of the second active layer, so that the second active layer is not easy to expand and deform. At the same time, the second active layer that is not easy to expand and deform is provided on the outside of the first active layer, so that the second active layer and the current collector cooperate with each other and act on the first active layer provided between the two at the same time, which well inhibits the expansion of the first active layer, and then inhibits the expansion of the negative electrode sheet as a whole, and improves the overall cycle performance of the battery.
[0064] On the other hand, the provision of binder A and binder B in the first active layer can not only improve the bonding effect between the first active layer and the second active layer and the current collector, but also ensure the bonding effect between the components within the first active layer itself, which helps to prevent the first active layer from being delaminated and cracked due to the expansion of the active material, and can further ensure the restraint effect of the second active layer and the current collector on the first active layer, preventing the first active layer from expanding. Avoid the situation of material falling and demolding of the negative electrode sheet.
[0065] like Figure 1 As shown, the second aspect of the present application provides a method for preparing the negative electrode sheet provided in the first aspect, comprising the following steps:
[0066] S1, mixing a first active material, a first binder, and a first conductive agent to form a first slurry;
[0067] S2, mixing a second active material, a second binder, and a second conductive agent to form a second slurry;
[0068] S3, sequentially coating the first slurry and the second slurry on the current collector;
[0069] S4. Drying to obtain the negative electrode sheet.
[0070] It is understandable that a solvent is added during the process of mixing the first active material, the first binder, and the first conductive agent, and the process of mixing the second active material, the second binder, and the second conductive agent.
[0071] In the present application, there is no particular limitation on the type of the above-mentioned solvent, and any known solvent can be used in the present application without violating the inventive concept of the present application. For example, the above-mentioned solvent is deionized water.
[0072] In the process of preparing the negative electrode sheet of the present application, after applying the second slurry before the first slurry is dried, the drying is completed at one time, so that the first slurry forms a first active layer on the surface of the negative electrode current collector, and the second slurry forms a second active layer on the surface of the first active layer away from the current collector. In this way, a fusion portion can be formed at the interface where the first active layer and the second active layer contact. The fusion portion includes not only the first binder in the first active layer, but also the carbon nanotubes in the second active layer. The carbon nanotubes are combined with the active layer, which can further strengthen the bonding strength between the first active layer and the second active layer to prevent expansion and slag falling. It also helps to increase the binding effect of the second active layer on the first active layer, reduce the expansibility of the first active layer, and thus improve the cycle performance of the battery.
[0073] The third aspect of the present application provides a battery, comprising a positive electrode sheet, a negative electrode sheet and a solid electrolyte membrane, wherein the negative electrode sheet is the negative electrode sheet provided in the first aspect or the negative electrode sheet prepared according to the preparation method provided in the second aspect.
[0074] The positive electrode sheets and the negative electrode sheets are cross-stacked, and the solid electrolyte membrane is arranged between the positive electrode sheets and the negative electrode sheets.
[0075] The present application has no particular limitation on the positive electrode sheet, which is usually composed of a positive electrode current collector and a positive electrode active material layer. The positive electrode active layer is arranged on the positive electrode current collector, and the side away from the positive electrode current collector faces the negative electrode sheet.
[0076] In some embodiments, the positive electrode current collector is generally made of a conductive metal foil, illustrative examples of which include copper foil, aluminum foil, stainless steel, and the like.
[0077] In some embodiments, the positive electrode active material layer generally includes a positive electrode active material, a positive electrode conductive agent, and a positive electrode binder. The positive electrode active material includes but is not limited to LiCoO 2 、LiMnO 2 、LiNiO 2 、LiVO 2 、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 、LiMn 2 O 4 、LiTi 5 O 12 、Li(Ni 0.5 Mn 1.5 ) 4 、LiFePO 4 、LiMnPO 4 、LiNiPO 4 、LiCoPO 4 、LiNbO 3or any one or a combination of at least two of the sulfur-carbon composite materials. 2 、LiMnO 2 、LiNiO 2 、LiVO 2 and LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 With rock salt layered structure, LiMn 2 O 4 、LiTi 5 O 12 and Li(Ni 0.5 Mn 1.5 ) 4 With spinel structure, LiFePO 4 、LiMnPO 4 、LiNiPO 4 、LiCoPO 4 and LiNbO 3 It has an olivine structure. Without violating the inventive concept of the present application, any known positive electrode active material can be applied to the present application.
[0078] In some embodiments, the positive electrode binder in the positive electrode active layer can improve the bonding between the positive electrode active materials and also improve the bonding between the positive electrode material layer and the positive electrode current collector.
[0079] In some embodiments, non-limiting examples of the positive electrode binder include polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, and the like.
[0080] In some embodiments, the positive electrode conductive agent in the positive electrode active layer can improve the electrode conductivity of the positive electrode sheet.
[0081] The positive electrode conductive agent may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.
[0082] In some embodiments, the solid electrolyte membrane includes a solid electrolyte. It is understood that the present application does not specifically limit the solid electrolyte material in the solid electrolyte membrane. Without violating the inventive concept of the present application, the solid electrolyte materials in the known solid electrolyte membrane are within the protection scope of the present application, which is only used as an illustrative example rather than a limitation on the protection scope. The solid electrolyte in the solid electrolyte membrane includes but is not limited to a polymer solid electrolyte, an oxide solid electrolyte, a sulfide solid electrolyte, etc.
[0083] The polymer solid electrolyte includes at least one of polyvinyl chloride (PVC), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), and polyethylene oxide (PEO).
[0084] The oxide solid electrolyte may include one or more garnet ceramics, LISICON type oxides, NASICON type oxides and perovskite type ceramics. For example, one or more garnet ceramics may be selected from the group consisting of: Li 6.5 La 3 Zr 1.75 Te 0.25 O 12 , Li 7 La 3 Zr 2 O 12 , Li 6.2 Ga 0.3 La 2.95 R 0.05 Zr 2 O 12 , Li 6.85 La 2.9 Ca 0.1 Zr 1.75 Nb 0.25 O 12 , Li 6.25 Al 0.25 La 3 Zr 2 O 12 , Li 6.75 La 3 Zr 1.75 Nb 0.25 O 12 , Li 6.75 La 3 Zr 1.75 Nb 0.25 O 12 And combinations thereof. One or more LISICON-type oxides may be selected from the group consisting of: Li 14 Zn(GeO 4 ) 4 , Li3+x (P 1-x Si x ) 4 (where 0<x<1), Li 3+x Ge x V 1-x O 4 (where 0<x<1) and combinations thereof. One or more NASICON-type oxides may be LiMM′(PO 4 ) 3 Definition, wherein M and M' are independently selected from Al, Ge, Ti, Sn, Hf, Zr and La. For example, in certain variations, one or more NASICON-type oxides may be selected from the group consisting of: Li 1+x Al x Ge 2-x (PO 4 ) 3 (LAGP) (where 0≤x≤2), Li1+xAlxTi2-x(PO4)3(LATP) (where 0≤x≤2), Li1+xYxZr2-x(PO4)3(LYZP) (where 0≤x≤2), Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 、LiTi 2 (PO 4 ) 3 、LiGeTi(PO 4 ) 3 ,LiGe 2 (PO 4 ) 3 、LiHf 2 (PO 4 ) 3 And combinations thereof. One or more perovskite ceramics may be selected from the group consisting of: Li 3.3 La 0.53 TiO 3 、LiSr 1.65 Zr 1.3 Ta 1.7 O 9 , Li 2x-y Sr 1-x Ta y Zr 1-y O 3 (where x = 0.75y and 0.60 < y < 0.75), Li 3 / 8 Sr 7 / 16 Nb 3 / 4 Zr 1 / 4 O 3 , Li3x La (2 / 3-x) TiO 3 (where 0<x<0.25) and their combinations.
[0085] The sulfide solid electrolyte may include one or more sulfide-based materials selected from the group consisting of: Li 2 SP 2 S 5 , Li 2 SP 2 S 5 -MS x (where M is Si, Ge and Sn and 0≤x≤2), Li 3.4 Si 0.4 P 0.6 S 4 , Li 10 G 2 S 11.7 O 0.3 , Li 9.6 P 3 S 12 , Li 7 P 3 S 11 , Li 9 P 3 S 9 O 3 , Li 10.35 Si 1.35 P 1.65 S 12 , Li 9.81 Sn 0.81 P 2.19 S 12 , Li 10 (Si 0.5 Ge 0.5 ) 2 S 12 、Li(Ge 0.5 Sn 0.5 ) 2 S 12 、Li(Si 0.5 Sn 0.5 )PsS 12 , Li 10 G 2 S 12 (LGPS), Li 6 PS 5X (wherein X is Cl, Br or I), Li 7 P 2 S 8 I. Li 10.35 Ge 1.35 P1.65 S 12 , Li 3.25 Ge 0.25 P 0.75 S 4 , Li 10 SnP 2 S 12 , Li 10 SiP 2 S 12 , Li 9.54 Si 1.74 P 1.44 S 11.7 C 10.3 and their combinations.
[0086] The present application will be further described below with reference to specific embodiments and comparative examples.
[0087] Example 1
[0088] The first active material particles, the first conductive agent SP, and the first binder are mixed in a mass percentage of 95:1:4 and added to a solvent to form a first slurry. The first active material particles include graphite and silicon carbide in a mass percentage of 75:25. The binder A and the binder B included in the first binder are both PAA.
[0089] The second active material particles, the second conductive agent, and the second binder PAA with a mass percentage of 96:1:3 are mixed and added to the solvent to form a second slurry. Among them, the second active material particles include graphite and silicon carbide with a mass percentage of 75:25. The second conductive agent includes single-walled carbon nanotubes and SP with a mass ratio of 1:1. The above-mentioned first slurry and second slurry are coated on the current collector in sequence, and the second slurry is coated on the top of the first slurry before the first slurry is dried, and dried together to form a negative electrode sheet.
[0090] Example 2
[0091] The difference from Example 1 is that the first binder includes a binder A and a binder B in a mass ratio of 1:3, wherein the binder A is SBR and the binder B is PAA.
[0092] Example 3
[0093] The difference from Example 1 is that the first binder includes a binder A and a binder B in a mass ratio of 1:3, wherein the binder A is SBR and the binder B is PAA. The first conductive agent also includes single-walled carbon nanotubes, wherein the mass ratio of the single-walled carbon nanotubes to SP is 1:1.
[0094] Example 4
[0095] The difference from Example 1 is that the first conductive agent further includes single-walled carbon nanotubes, wherein the mass ratio of the single-walled carbon nanotubes to the SP is 1:1.
[0096] Comparative Example 1
[0097] The difference from the first embodiment is that the second conductive agent is SP.
[0098] Comparative Example 2
[0099] The difference from Comparative Example 1 is that the first conductive agent further includes single-walled carbon nanotubes, wherein the mass ratio of the single-walled carbon nanotubes to the SP is 1:1.
[0100] The test parameters of the embodiments and comparative examples are summarized in Table 1 below:
[0101] Table 1
[0102]
[0103] Preparation of a battery: A battery is prepared using the negative electrode sheet prepared in the above embodiment and proportion, specifically comprising the following steps:
[0104] The positive electrode sheet, solid electrolyte membrane and negative electrode sheet are stacked in order so that the solid electrolyte membrane is between the positive and negative electrode sheets, and then they are wound to obtain a bare battery cell. After welding the pole ears, the bare battery cell is placed in an outer packaging foil aluminum-plastic film, and after vacuum packaging, standing, formation, shaping, capacity testing and other processes, a soft-pack solid-state battery is obtained.
[0105] Test Case
[0106] The above-mentioned embodiments and comparative examples were subjected to cycle performance test, cycle expansion force test and interface condition observation respectively.
[0107] 1. Cycle performance test:
[0108] The lithium ion batteries obtained in the above examples and comparative examples were subjected to cycle performance tests:
[0109] S1: At room temperature, charge to the final voltage with a charging current of 1C, a cut-off current of 0.05C, and let stand for 30 minutes;
[0110] S2: Discharge at 1C to the final discharge voltage, record the discharge capacity, and let stand for 30 minutes;
[0111] The steps S1-S2 are performed cyclically until the discharge capacity decreases to 80% of the initial discharge capacity, then the experiment is terminated and the final number of cycles is recorded.
[0112] 2. During the cycle performance test, the battery is assembled into a steel plate fixture, and a pressure sensor is placed between the steel plate fixture and the battery. The pressure sensor is connected to a computer to test the expansion force of the battery during the cycle.
[0113] 3. After the cycle is completed, dissect the lithium-ion battery to check the interface of the battery electrode.
[0114] Table 2
[0115]
[0116] Table 2 shows the experimental results of various embodiments and comparative examples.
[0117] By comparing Example 1 with Comparative Example 1, and Example 4 with Comparative Example 2, it can be seen that adding single-walled carbon nanotubes in the second active layer inhibits the expansion of the second active layer, while also having a certain binding effect on the negative electrode material of the first active layer, which can significantly reduce the cycle expansion force, thereby improving the cycle performance.
[0118] By comparing Example 1 with Example 2, and Example 3 with Example 4, it can be seen that the first binder in the first active layer uses a dual binder of SBR and PAA, which can improve the problem of edge dropout. It also increases the bonding effect between the first active layer and the second active layer and the current collector, which can further strengthen the binding of the second active layer and the current collector to the first active layer, so that the battery cycle performance is further improved.
[0119] By comparing Example 2 and Example 3, it can be seen that adding single-walled carbon nanotubes to the first active layer can significantly improve the cycle performance of the battery.
[0120] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0121] The above embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.
Claims
1. A negative electrode sheet, characterized in that: It includes a current collector and a first active layer and a second active layer sequentially arranged on the surface of the current collector; The first active layer includes a first active material, a first conductive agent and a first binder, and the first binder is a mixture of a binder A and a binder B; The second active layer includes a second active material, a second conductive agent and a second binder, and the second conductive agent includes single-walled carbon nanotubes.
2. The negative electrode sheet according to claim 1, characterized in that: The first conductive agent includes single-walled carbon nanotubes.
3. The negative electrode sheet according to claim 1, characterized in that: The binder A and the binder B are different binders, and the binder A includes at least one of a PAA binder or an SBR binder; The binder B includes at least one of a PAA-based binder and a SBR-based binder.
4. The negative electrode sheet according to claim 1, characterized in that: In the first binder, the mass ratio of the binder A to the binder B is 1:
3.
5. The negative electrode sheet according to claim 1, characterized in that: The mass ratio of the first conductive agent to the first binder is 1:4; The mass ratio of the second conductive agent to the second binder is 1:
3.
6. The negative electrode sheet according to claim 1, characterized in that: The first active material includes one or more of pure silicon, silicon alloy, silicon-carbon composite material, and silicon-oxygen composite material; the second active material includes one or more of pure silicon, silicon alloy, silicon-carbon composite material, and silicon-oxygen composite material.
7. The negative electrode sheet according to claim 1, characterized in that: The mass percentage of the first active material and the first binder is (93%-97%): (2%-5%).
8. The negative electrode sheet according to claim 1, characterized in that: The mass percentage of the second active material and the second conductive agent is (93%-97%): (1%-2%).
9. A method for preparing a negative electrode sheet according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, mixing a first active material, a first binder, and a first conductive agent to form a first slurry; S2, mixing a second active material, a second binder, and a second conductive agent to form a second slurry; S3, sequentially coating the first slurry and the second slurry on a current collector; S4. Drying to obtain the negative electrode sheet.
10. A battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet and a solid electrolyte membrane, wherein the negative electrode sheet is the negative electrode sheet according to any one of claims 1 to 8 or the negative electrode sheet prepared according to the preparation method according to claim 9.
Citation Information
Cited By
Silicon-based negative pole piece, preparation method thereof and sulfide all-solid-state battery
CN122267092A